Philosophy and the Implementation of Marxism-Leninism in Lithuania’s Higher Education Institutions from 1944 to 1947 - Peluritis, Laurynas (Lietuvos istorijos studijos, 2021)
The article examines the introduction of Soviet Marxism (Marxism-Leninism) into the Lithuanian higher education system in 1944–1947. Based on archival sources and existing historiography, this paper explores the development of the higher education system in Lithuania during the first years of the Soviet occupation, including the translation, publication, and dissemination of ideological texts. It is argued that the introduction of Soviet Marxism in Lithuanian higher education institutions in 1944–1945 was carried out in a forced and chaotic manner, the organization of teaching and the preparation of ideological literature was slow, and there was a lack of staff to teach ideological courses. First came the creation of formal institutions (departments, divisions, institutes), and only then a consistent introduction of Marxist-Leninist teachings and the implementation of ideological control.